« Ne se dit qu’en parlant des monuments » ? Les hauts et les bas de l’ethos viril de l’écrivain dans la correspondance de Gustave Flaubert et Louise Colet - Christèle Couleau (Argumentation et Analyse du Discours, 2023)
In his long correspondence with Louise Colet, Flaubert establishes a double ethos of lover and author. These two facets are linked, around the virility key issue: they highlight the same claim to singularity; they enable the lover to slide from self-justification to a discourse of mastery; and the gender difference provides stereotypical structures likely to consolidate his authority, both in relation to his partner and to the contemporary literary field. Ethos is constructed dynamically and differentially, in a process of negotiation that closely involves his partner.